Applications of NILM Techniques to Energy Management and Assisted Living. Issue 11 (2019) - Hernández, Á.; Ruano, A.; Ureña, J.; Ruano, M.G.; Garcia, J.J.
Abstract: Electricity disaggregation is the process of separating the total electrical load of a single household into appliance specific loads. This can be achieved either by intrusive monitoring of each appliance via individual device load meters or by employing Non-Intrusive Load Monitoring (NILM) techniques, that perform a detailed analysis of the current and voltage of the total load, typically measured at the interface to the power source. NILM techniques are becoming recognized tools for several applications, from which their use in Home Energy Management Systems and Ambient Assisted Living clearly stand out. The objective of this paper is that, by reviewing the most recent research and development in NILM and in its applications, to foster further interest in this technology.